Host and pathogen autophagy are central to the inducible local defences and systemic response of the giant kelp Macrocystis pyrifera against the oomycete pathogen Anisolpidium ectocarpii - Murúa, Pedro (The New phytologist, 2020)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.